2022
DOI: 10.1177/11782218221095873
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects Associated With Kratom (Mitragyna speciosa) and Polysubstance Use: A Narrative Review

Abstract: Background: Kratom ( Mitragyna speciosa) consumption and associated health effects have raised debates in the United States. Although most people using this herb do not experience adverse health effects associated with kratom use, medical providers should be knowledgeable of emerging substances and concurrent, sequential, or simultaneous use of other drugs which may impact healthcare recommendations and prescribing practices. Methods: The objective of this narrative review was to elucidate selected health effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Medical providers should be aware of emerging substances and concurrent, sequential, or simultaneous use of other drugs which may impact healthcare recommendations and prescribing practices (Striley et al, 2022)…”
Section: Kratom Safetymentioning
confidence: 99%
“…Medical providers should be aware of emerging substances and concurrent, sequential, or simultaneous use of other drugs which may impact healthcare recommendations and prescribing practices (Striley et al, 2022)…”
Section: Kratom Safetymentioning
confidence: 99%
“…Kratom ( Mitragyna speciosa ) is a psychoactive herb that some people report using to manage psychiatric symptoms, treat pain, or reduce the use of other substances 1,2 . In the United States (US), past‐year prevalence of kratom use is estimated to be 0.7–4.1% 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the United States (US), past‐year prevalence of kratom use is estimated to be 0.7–4.1% 3 . Most people using kratom do not experience negative health effects, 1 a growing amount of clinical and/or forensic literature elucidates adverse outcomes—including mortality—when kratom was used with other substances 2,4,5 . For instance, Corkery et al found that polysubstance use (PSU) was present in 87.2% of known kratom‐associated fatalities 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations